Impact of forest fertilizers on winter pastures of semi-domesticated reindeer - Eriksson, Olof; Raunistola, Tuomo (Rangifer, 1993)
The effects of forest fertilizers on Calluna vulgaris, Vaccinium vitis-idaea, Cladina arbusculua, Cladina rangiferina and Cladina stellaris were studied during an eleven-year experimental period in Vasterbotten, Sweden. The study site was situated in the boreal region and was part of a 130 years old Pinus sylvestris stand. The forest type is mainly the dry dwarf-shrub type. Thirty-two demarcated plots (20 m x 20 m) were grouped into eight blocks, each containing four plots. In 1979 and 1985 fertilizations with ammonium nitrate equiavalent to 150 kg N/ha, with ammonium nitrate equiavalent to 250 kg N/ha and with urea equiavalent to 150 kg N/ha were carried out. Field sampling wad done in late July 1979, 1980, 1982, 1984, 1985, 1986, 1988 and 1990. Main parameters studied were coverage, height and standing crop. Effects were visible already after one growing season. All treatments had a positive effect on the growth of C. vulgaris and V. vitis-idaea. Doses around or over 150 kg N/ha, gave a clearly negative effect (range 23% - 73%) on the standing crop of Cladina spp. for a period of time exceeding eleven years compared to the control standing crop.